Protection against oxidative stress in hepatic and pancreatic cells by selected plant-derived chemicals - Adomako-Bonsu, Amma Gyapomah (2016)
Persistent accumulation of free radicals in cells leads to oxidative stress, which plays a causative role in the induction and progression of various chronic diseases. Therapeutic focus has therefore shifted towards the use of antioxidants, with recent interest in those of plant origin. This study investigated radical scavenging and cytoprotective activities of phytochemicals (quercetin, curcumin, sulforaphane, rosmarinic acid, caffeic acid, danshensu (3,4-dihydroxyphenyllactic acid), ferulic acid and m-coumaric acid) against DPPH free radical in a non-cellular assay, and oxidative damage in hepatic (HepG2) and pancreatic (1.1B4) cells, elicited by an organic hydroperoxide (tert-butylhydroperoxide - tBHP) and a more physiologically relevant stressor (palmitate). Direct and indirect cytoprotective activities were assessed by neutral red viability assay after 5 h co-exposure and 20 h pre-exposure conditions, respectively.